(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Transparency considered being one of the modern administrational terms which started to be largely used in the last period, because of its political, economical, social and cultural dimensions. As well as, its administrational dimension that helps to create a work environment marked by order and flawless from wrong practices and Transparency provides credibility to the sides that pursue it in their practices, till it became a mean of distinction. The choice of the subject of the research ((Transparency and its effect on Level of Job satisfactions of Workers in General Insurance company)), which aims to measure the effect of Transparency in Level of Job satisfactions of Workers in Insurance company. Came in the time when many countries tend to depend on services in their economics to obtain the per mentioned aim of the research, a hypothetical model was built, that involved the dependent and independent variables and sub variables. One main hypothesis is formulated. To test the validity of hypotheses, one random sample was chosen. The sample which consists of 46 individuals presented general managers, branches managers and workers in General insurance companies)).The information’s about the sample of research was collected by using the Questionnaire and a collection of annual reports, and data were processed by using a group of unparametrice and descriptive statistical means to study the effect between the research variables .